A novel fluorescent metal-organic framework based on porphyrin and AIE for ultra-high sensitivity and selectivity detection of Pb2+ ions in aqueous solution. (December 2021) - Wang, Qianyi; Ke, Weiquan; Lou, Hengyi; Han, Yihui; Wan, Junmin
Abstract: Lead (Pb 2+ ) ion, as a heavy metal pollutant in water, is harmful to human health, and may cause various diseases. Therefore, it is of great necessity for people to find a new and quick way to detect Pb 2+ ions in water. Based on this condition, a zinc porphyrin-based metal-organic framework (ZnTCPP-MOF) with aggregation-induced emission (AIE) was successfully synthesized via coordination polymerization of zinc (Zn 2+ ) ions, H2 TCPP and TPE-2COOH, and shows a great fluorescent phenomenon which can be used as a fluorescent probe to detect metal ions in aqueous solution. So, the ZnTCPP-MOF with a highly selective and sensitive property can be employed to detect Pb 2+ ions. The experiment results exhibit that the color change of ZnTCPP-MOF could be directly discovered from bright red to colorless after adding Pb 2+ ions by naked eyes. Meanwhile, the quenching curves, at lower concentrations of Pb 2+ ions, exhibited an excellent linear relationship between fluorescence quenching efficiency and concentrations. The highlight of this study is that the ZnTCPP-MOF could explore Pb 2+ ions in water, at very low concentrations, as well as the limit of detection (LOD) is 4.99 × 10 −8 M which is an excellent data, compared with other MOFs. Highlights: A novel metal-organic framework (MOF) with an excellent fluorescence performance was prepared. The ZnTCPP-MOF with a highly selective and sensitive property can be employed to detect Pb 2+ ions in water. The result of ZnTCPP-MOF detecting Pb 2+ ions in water is viewed by naked eyes. The limit of detection (LOD) has been found in a lower scope which is 4.99 × 10 −8 M, compared with other MOFs.